Strategi Adaptasi Ekonomi Keluarga Miskin Kota Pada Masa Pandemi Covid-19 - Firdaus W. Suhaeb (Research Agency for Humanity and Urban, 2023)
This research study aims to describe and analyze the economic adaptation strategies of urban poor families during the Covid-19 pandemic through the concept of a livelihood strategy. This research uses a descriptive-qualitative type of research. The research informants were selected intentionally on 10 urban poor/vulnerable families who were beneficiaries of Social Cash Assistance and had household-based small businesses. Data collection techniques, namely observation, interviews, documentation. Data analysis techniques, namely descriptive-qualitative analysis through the stages of data reduction, data presentation, and conclusions. The results of this study show the economic adaptation strategy of poor families in cities beneficiaries of Social Cash Assistance (BST) during the Covid-19 pandemic in Manggala District, Makassar City carried out by their families through a double pattern of living by utilizing the Cash Social Assistance fund to open a household-based small business and to increase the capital of small businesses that have been initiated so far, as well as working part-time as day laborers, washing laborers, and members of Makassar Recover to supplement their family income. While the social network livelihood strategy, they do it by utilizing existing relationships and social relationships to get jobs and orders and assistance in the form of basic necessities and sometimes money from the government. The expected economic stability of the family has an impact on the implementation of adaptation strategies seen in terms of education, income, employment, and family housing during the pandemic.